1989
DOI: 10.1161/01.hyp.14.5.472
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic factors in renovascular fibromuscular dysplasia. A case-control study.

Abstract: The role of several factors that have been suggested as being of etiologic importance in renovascular fibromuscular dysplasia was examined in a case-control study of 33 patients with angiographically demonstrated fibromuscular dysplasia and 61 renal transplant donor control subjects with normal renal arteries. The factors studied included use of oral contraceptive agents or markers of sex hormone dysfunction, mechanical stress to the renal artery wall, human lymphocytic antigen (HLA) type, cigarette smoking, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
2
6

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 38 publications
1
101
2
6
Order By: Relevance
“…This study found a lower prevalence of smoking in FMD patients than previous studies (approx 50% vs 70-80% in other studies [4][5][6] ), possibly as a result of effective anti-smoking campaigns by the National Heart Foundation of Australia. The fact that over half the patients with multifocal lesions had never smoked proves conclusively that a personal history of smoking is not essential for the development of FMD.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…This study found a lower prevalence of smoking in FMD patients than previous studies (approx 50% vs 70-80% in other studies [4][5][6] ), possibly as a result of effective anti-smoking campaigns by the National Heart Foundation of Australia. The fact that over half the patients with multifocal lesions had never smoked proves conclusively that a personal history of smoking is not essential for the development of FMD.…”
Section: Discussioncontrasting
confidence: 71%
“…Nicholson et al 5 found a significantly higher percentage of smokers in female FMD patients (71% of 21) than in female controls (41% of 158, P Ͻ 0.0005). Sang et al, 6 in a case-control study of 33 FMD patients (15 with beaded lesions) and 61 renal transplant donor controls, found not only a significantly higher percentage of smokers in the FMD group (79% vs 53%, P = 0.003) but also a positive relationship between pack years of smoking and the presence of FMD (P Ͻ 0.001).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations